PENGARUH NON-DEBT TAX SHIELDS DAN KARAKTERISTIK PERSONAL CHIEF EXECUTIVE OFFICER TERHADAP FINANCIAL LEVERAGE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - DIANA, ERIKA; Hastuti, Cut Sri Firman (Universitas Teuku Umar, 2019)
Abstract: This study aims to examine the effect of non-debt tax shields and personal characteristics of the chief executive officer on final leverage on manufacturing companies listed on the Indonesia stock exchange in 2013-2017. The type of research used is hypothesis testing. The sample chosen using purposive sampling is as many as 70 companies. Data obtained from annual reports and analyzed using multiple linear regression analysis methods. The results of the study show that non-debt tax shields affect financial leverage, while the gender chief executive officer, experience of the chief executive officer has no effect on financial leverage. Keyword: Financial Leverage, Non-Debt Tax Shields and Character Personal Chief Executive Officer Abstrak: Penelitian ini bertujuan untuk menguji pengaruh non-debt tax shields dan karakteristik personal chief executive officer terhadap finalcial leverage pada perusahaan manufaktur yang terdaftar di bursa efek Indonesia tahun 2013-2017. Jenis penelitian yang digunakan adalah pengujian hipotesis. Sampel yang dipilih menggunakan purposive sampling yaitu sebanyak 70 perusahaan. Data diperoleh dari laporan tahunan dan dianalisis menggunakan metode analisis regresi linear berganda. Hasil penelitian menunjukkan non debt tax shields berpengaruh terhadap financial leverage, sedangkan gender chief executive officer, pengalaman chief executive officer tidak berpengaruh teradap financial leverage. Kata Kunci: Financial Leverage, Non-Debt Tax Shields dan Karakter Personal Chief Executive Officer.